Droplet transport by bendotaxis - Bradley, A (2020)
In this thesis, we study bendotaxis – a novel, passive droplet transport mech- anism driven by the coupling between capillary pressure within the droplet and bending deformations of the channel confining it. This mechanism is inspired by observations of the legs of Gerris Regimis, which are covered in setae rendering them superhydrophobic; the setae deform by bending in re- sponse to the capillary pressure of vapour droplets as they condense between setae, resulting in their dynamic expulsion, and thus helping to maintain a superhydrophobic leg.